2006
DOI: 10.1002/cphc.200500720
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Decarbonylation of Acetaldehyde by Fe+ and Cr+

Abstract: We report a comprehensive theoretical study on the decarbonylation of acetaldehyde by Fe+ and Cr+. Various intermediates, transition states, and products involved in the decarbonylation reactions are fully optimized at the B3LYP/6-311+G(2df,2pd) level of theory. The potential energy surfaces (PESs) corresponding to [M,O,C2,H4]+(M=Cr and Fe) are examined in detail using B3LYP and CCSD(T) methods, respectively. The validity of these theoretical methods is calibrated with respect to the available thermochemical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…To better understand the fundamental aspects of this reaction, several studies have been reported on the investigation of the relevant mechanism [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. As one of the sim ple carbonyl containing organic molecules, acetalde hyde is used in many practical application fields such as organic synthesis, catalysis, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the fundamental aspects of this reaction, several studies have been reported on the investigation of the relevant mechanism [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. As one of the sim ple carbonyl containing organic molecules, acetalde hyde is used in many practical application fields such as organic synthesis, catalysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since catalytic hydrogenation of carbon monoxide as well as C-H activation of aldehydes is usually promoted by metal bearing catalysts, it is interesting and instructive to explore the reactions of gas phase transition metal cations and atoms with aldehyde, which may lead to a better understanding of fundamental aspects of ele mentary transition metal reactions initiated by C-H insertion. Earlier studies have focused mainly on the reactions between acetaldehyde and first row transi tion metal cations such as Co + , Fe + , Cr + , Ti + , and Ni + et al [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The 3,1-H 2 elimination channel from 17 involves a subsequent 1-H migration to form intermediate 19 via a six-membered-ring transition state, TS 17-19 , which lies 6.8 kcal/mol below TS 17-18 or 7.6 kcal/mol above the entrance channel. Similar to 18, species 19 is also a direct precursor of the dehydrogenation products: Co + (CHCHCHNH 2 ) + H 2 (4)(5)(6)(7)(8), which is calculated to be 20.4 kcal/mol exothermic from the separated reactants. Now we consider the initial 2-C-H migration mechanisms.…”
Section: Loss Of C 2 H 2 Pes For This Elimination Is Given Inmentioning
confidence: 99%
“…Introduction G as-phase studies on transition metal ions or metal-ligand complex mediated bond breaking and bond making processes of ''isolated'' ionmolecule reactions, provide valuable insight into the nature of fundamental organometallic and catalytic reactions [1][2][3][4][5]. With regard to small oxygencontaining molecules, the gas-phase reactions of aldehydes, ketones, and ethers with different metal ions have been widely investigated [6][7][8][9][10][11][12][13]. Previous experimental studies involved the use of Fourier transform ion cyclotron resonance and ionbeam experiments by Beauchamp, Schwarz, and Freiser [6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…Recent progress has involved density functional theory (DFT) to offer complementary information on the structure and energy details of the potential energy surfaces (PESs) for the reactions. Recently, the demethanation mechanism of dimethyl ether and acetaldehyde mediated by late first row transition metal ions were investigated by B3LYP in conjunction with proper basis set [12][13][14][15].…”
mentioning
confidence: 99%